Opportunities for agrivoltaic systems to achieve synergistic food-energy-environmental needs and address sustainability goals - Walston, Leroy J.; Barley, Tristan; Bhandari, Indraneel; Campbell, Ben; McCall, James; Hartmann, Heidi M.; Dolezal, Adam G. (Frontiers in Sustainable Food Systems, 2022)
Achieving decarbonization goals to address global climate change and increasing energy needs requires significant continued investments in solar energy. The expansion of utility-scale solar development across the globe has increased the pressure on land resources for energy generation and other land uses (e.g., agriculture, biodiversity conservation). To address this growing issue, greater emphasis has been placed on solar development strategies that maximize the benefits of solar energy generation and multiple ecosystem services, such as the development of agrivoltaics systems that co-locate solar energy production and various forms of conservation and agricultural land uses. The purpose of this paper is to systematically synthesize the potential ecosystem services of agrivoltaics and summarize how these development strategies could address several United Nations Sustainable Development Goals (SDGs). Our review will focus on four broad potential ecosystem services of agrivoltaics: (1) energy and economic benefits; (2) agricultural provisioning services of food production and animal husbandry; (3) biodiversity conservation; and (4) regulating ecosystem services such as carbon sequestration and water and soil conservation. In particular, we will highlight the state of the science, challenges, and knowledge gaps that represent opportunities for further study to better understand how solar energy deployment can facilitate sustainable development.